(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Despite significant advances in systemic therapies, radiation oncology, and surgical techniques, many patients with cancer are still incurable. A novel therapeutic approach has been to target the vascular endothelial growth factors (VEGFs) which are often mutated and/or over-expressed in many tumors. The ligands and receptors of VEGF family are well established as key regulators of angiogenesis and vasculogenesis processes. VEGF is a homodimeric, basic, 45 kDa glycoprotein specific for vascular endothelial cells. Specifically, VEGF participates in regulation of the female reproductive cycle, wound healing, inflammation, vascular permeability, vascular tone, hematopoiesis and also contributes to pathological angiogenesis disorders such as cancer, rheumatoid arthritis, diabetic retinopathy and the neovascular form of macular degeneration. Thus, the role of VEGF has been extensively studied in the pathogenesis and angiogenesis of human cancers. Clinical trials have anti-VEGF therapies are effective in reducing tumor size, metastasis and blood vessel formation. Clinically, this may result in increased progression free survival, overall patient survival rate and will expand the potential for combinatorial therapies. The aim of present review is on the cellular responses of VEGF inhibitors and their implications for cancer therapy.